In"tarot"ception – Primer, Learning Module, Philosophical Foundations and Application - Bettinger, Jesse (Journal of NeuroPhilosophy, 2023)
Perception operates in general according to two causal processes—bottom-up (sensory driven; progressive), and top-down (anticipatory; inferential; with signal progression issuing from expectations about future states). Both are essential to consciousness. Like colors, there are, in essence, three primary modes of perception. Exteroception, interoception and proprioception. The interoceptive faculty of perception refers to the moment-to-moment awareness of the body’s interior dynamics in concert with regulatory homeostatic and allostatic operations that furnish a core feature of subjective experience, social navigation and sense-of-self. This paper provides an overview of interoception accompanied by a visual diagram that serves as a heuristic learning model for conceptually organizing the materials. This follows with a summary of A.N. Whitehead’s ’three modes of perception’ that clarifies the connections with interoception to such an extent they may be regarded as philosophical foundations. This is followed by the topics of information integration and biological intuition.